Calcineurin inhibitor Tacrolimus impairs host immune response against urinary tract infection - Emal, Diba; Rampanelli, Elena; Claessen, Nike; Bemelman, Frederike J.; Leemans, Jaklien C.; Florquin, Sandrine; Dessing, Mark C. (Scientific reports, 2019)
Calcineurin inhibitor Tacrolimus, is a potent immunosuppressive drug widely used in order to prevent acute graft rejection. Urinary tract infection (UTI) is the most frequent infectious complication in renal transplant patients and long-term use of Tacrolimus might be involved in higher susceptibility to bacterial infections. It remains largely unknown how Tacrolimus affects the host innate immune response against lower and upper UTI. To address this issue, we used experimental UTI model by intravesical inoculation of uropathogenic E . coli in female wild-type mice pre-treated with Tacrolimus or solvent (CTR). We found that Tacrolimus pre-treated mice displayed higher bacterial loads (cystitis, pyelonephritis and bacteremia) than CTR mice. Granulocytes from Tacrolimus pre-treated mice phagocytized less E . coli , released less MPO and expressed decreased levels of CXCR2 receptor upon infection. Moreover, Tacrolimus reduced TLR5 expression in bladder macrophages during UTI. This immunosuppressive state can be explained by the upregulation of TLR-signaling negative regulators (A20, ATF3, IRAK-M and SOCS1) and parallel downregulation of TLR5 as observed in Tacrolimus treated granulocytes and macrophages. We conclude that Tacrolimus impairs host innate immune responses against UTI.